1999
DOI: 10.2172/5824
|View full text |Cite
|
Sign up to set email alerts
|

Potential Hazards Relating to Pyrolysis of c-C{sub 4}F{sub 8} in Selected Gaseous Diffusion Plant Operations

Abstract: Boolean logic expressions are ollen derived in safety and reliability analysis. Since the values of the operands are rarely exact, accounting for uncertainty with the tightest justifiable bounds is important. Accurate determination of result bounds is difficult when the inputs have "constraints." One example of a constraint is that an uncertain variable that appears multiple times in a Boolean expression must always have the same value, although the value cannot be exactly specified. A solution for this "repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Under conditions at which fluorocarbons can thermally degrade (above a few hundred degrees Celsius), potentially hazardous unsaturated fluorocarbon compounds may form, most notably perfluoroisobutylene (PFIB; also known as perfluoroisobutene, octafluoroisobutene, and octafluoroisobutylene, or by its chemical formula, i-C 4 F 8 or iso-C 4 F 8 ). This degradation has been experimentally observed for c-C 4 F 8 , but chemical kinetics studies described by Trowbridge (1999a) suggest that the actual operations examined are unlikely to produce serious concentrations of PFIB. Rather, the main toxic decomposition products are likely to be HF or COF 2 .…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Under conditions at which fluorocarbons can thermally degrade (above a few hundred degrees Celsius), potentially hazardous unsaturated fluorocarbon compounds may form, most notably perfluoroisobutylene (PFIB; also known as perfluoroisobutene, octafluoroisobutene, and octafluoroisobutylene, or by its chemical formula, i-C 4 F 8 or iso-C 4 F 8 ). This degradation has been experimentally observed for c-C 4 F 8 , but chemical kinetics studies described by Trowbridge (1999a) suggest that the actual operations examined are unlikely to produce serious concentrations of PFIB. Rather, the main toxic decomposition products are likely to be HF or COF 2 .…”
Section: Introductionmentioning
confidence: 60%
“…Three candidates are presently being considered: cycloperfluorobutane (also known as FC-c318 or by its chemical formula, c-C 4 F 8 ), normal perfluorobutane (also known as FC-3110, n-C 4 F 10 , or simply as C 4 F 10 ), and perfluorotetrahydrofuran (also known as f-THF or c-C 4 F 8 O). Two earlier reports documented investigations into the thermal and chemical stability of c-C 4 F 8 at conditions expected to apply during the most severe high-temperature operations at the Portsmouth and Paducah Gaseous Diffusion Plants (Trowbridge 1999a) and in cascade operations (Trowbridge 1999b). This report documents a similar examination of the two additional coolant candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Pure c-C 4 F 8 , for example, is predicted to generate a constant-volume adiabatic equilibrium temperature of 1977 K simply by decomposition to C(s) and CF 4 . but, in fact, does not form these products at any significant rate even when heated to elevated temperatures (Trowbridge 1999b and references therein). At flame temperatures, however, formation of C(s) is sometimes observed.…”
Section: Comparison With Fixed Reaction Detonation Modelsmentioning
confidence: 99%
“…Trowbridge 18 conducted a literature survey of the decomposition of perfluorocyclobutane, perfluoroethylene and other polymeric perfluorocarbons such as PTFE. The presence of oxygen suppressed the formation of PFiB, but also led to the formation of other toxic compounds such as HF (hydrogen fluoride), CO (carbon monoxide), COF 2 (carbonyl fluoride), CF 4 (methane) and CO 2 (carbon dioxide).…”
mentioning
confidence: 99%
“…Trowbridge 19 later conducted an analysis of the reaction kinetics for additional 4-carbon compounds, namely c- With regards to the residence time, there have been several studies also on this topic. Hauptschein, et al, in their study found that for short duration, "flow-like" exposure conditions, perfluoropropene exposure to high temperature resulted in no decomposition, but batch reactions did.…”
mentioning
confidence: 99%